2020
DOI: 10.3390/s20143810
|View full text |Cite
|
Sign up to set email alerts
|

The Gaitprint: Identifying Individuals by Their Running Style

Abstract: Recognizing the characteristics of a well-developed running style is a central issue in athletic sub-disciplines. The development of portable micro-electro-mechanical-system (MEMS) sensors within the last decades has made it possible to accurately quantify movements. This paper introduces an analysis method, based on limit-cycle attractors, to identify subjects by their specific running style. The movement data of 30 athletes were collected over 20 min. in three running sessions to create an individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Even though the vast majority of the runs in the current study showed a transient effect, there are also participants who either had no initial oscillations or a mixed outcome with one run showing an effect whereas the other had none. This has also been shown in previous studies [ 3 , 12 ]. Vieten and Weich reported, that the starting value of the deflection is very subject-specific and influenced by randomness.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Even though the vast majority of the runs in the current study showed a transient effect, there are also participants who either had no initial oscillations or a mixed outcome with one run showing an effect whereas the other had none. This has also been shown in previous studies [ 3 , 12 ]. Vieten and Weich reported, that the starting value of the deflection is very subject-specific and influenced by randomness.…”
Section: Discussionsupporting
confidence: 91%
“…The functionality of the Attractor app is based on the Attractor Method developed by Vieten and colleagues [ 21 ] and is available online via . Further, a super attractor of each run was calculated to represent each participant’s individual gait-print as a mean attractor of all single minutes of each session [ 3 ]. To detect, quantify, and validate the transient effect of a running performance, three mathematical procedures were considered ( Figure 1 ):…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to identify individuals based on their movement patterns (gait recognition) has long fascinated society [1]. In biomechanics and biometrics, the mechanisms of human gait have been explored as biometric features and it has been demonstrated repeatedly that human gait is as unique to an individual as is their fingerprint [2][3][4]. Pataky and colleagues [5], for instance, showed that 104 individuals could be differentiated based only on their dynamic plantar pressure patterns with accuracy rates of over 99%.…”
Section: Introductionmentioning
confidence: 99%